2018
DOI: 10.1007/s11099-017-0734-z
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical changes and oxidative damage in four foxtail millet varieties following exposure to sethoxydim

Abstract: In order to assess its response to the herbicide, sethoxydim (SEY), seedlings of two foxtail millet (Setaria italica) hybrids were exposed to 0.75, 1.5, 3, and 6 L(SEY active ingredient, ai) ha -1 for 7 and 15 d. Our results showed that SEY reduced photosynthesis and oxidative stress in the hybrid millet (Zhangza) at the dosage below 1.5 L(ai) ha -1 (i.e., recommended dosage), whereas it caused death of Jingu 21 at all treatment dosages. In addition, we further explored the effect of SEY on PSI and PSII; the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…In the present study, fluroxypyr treatment caused the increase in Y(NO), which demonstrated that the plant cannot protect itself against damage from excess illumination due to blocking the regulatory mechanism of the non-photochemical dissipation of energy. Consistent with our results, Guo et al (2018) reported that sethoxydim has similar effects on the photosynthetic pigments, photosynthetic gas exchange and chlorophyll fluorescence parameters of foxtail millet.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, fluroxypyr treatment caused the increase in Y(NO), which demonstrated that the plant cannot protect itself against damage from excess illumination due to blocking the regulatory mechanism of the non-photochemical dissipation of energy. Consistent with our results, Guo et al (2018) reported that sethoxydim has similar effects on the photosynthetic pigments, photosynthetic gas exchange and chlorophyll fluorescence parameters of foxtail millet.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have demonstrated that excessive application of fluroxypyr in the environment inhibits plant growth (Wu et al, 2010; Guo et al, 2018). In the present study, we found that fluroxypyr had a slight effect on plant growth at relatively low doses, but exerted significant influence at high doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 min of dark adaptation, F 0 was measured. 29 Then, the maximum fluorescence yield of the dark-adapted state (F m ) was detected under a saturated pulse (4000 μmol m −2 s −1 ). Followed by 40 s of darkness, 1 s of activated light (270 μmol m −2 s −1 ), and one saturated pulse, the maximal fluorescence yield of the light-adapted state (Fm′) was detected.…”
Section: Detection Of Chlorophyll Fluorescence Parametersmentioning
confidence: 99%
“…Additionally, the hybrid foxtail millet called Zhangzagu is popular because of its high resistance, yield, and nutritional value (Dong et al, 2014;Guo et al, 2016). However, foxtail millet production in China is limited by factors, including severe weed infestation (Guo et al, 2018). Weeds reduce crop yield, quality, and the market value of foxtail millet.…”
Section: Introductionmentioning
confidence: 99%